Pengaruh Keikutsertaan Senam Hamil Terhadap Tingkat Kecemasan Ibu TM III Untuk Menghadapi Persalinan Di Klinik Kehamilan Sehat Serpong - Wulandari Rettob; Ling Ahmad Qosim; Nur Cahyani Ari Lestari (Jurnal Medika Nusantara, 2023)
According to WHO, in 2019 the maternal mortality rate in the world reached 303,000 people, the mortality rate in ASEAN was 235 per 100,000 births (ASEAN Secetariat, 2020). Meanwhile in Indonesia according to the Ministry of Health 2021, the maternal mortality rate increased by 7,389 cases or 305 per 100,000 live births. Quoted from the health profile of Banten 2021 MMR in Banten Province reached 576 cases. Many factors influence the high maternal mortality rate, one of which is the anxiety of pregnant women facing childbirth. This study aims to determine differences in anxiety levels in third trimester pregnant women who take part in pregnancy exercise and those who do not take part in pregnancy exercise in dealing with labor. The study used a quasi-experimental design (Almost experimental design) with approachnon equivalent control group design. This research consisted of 2 treatment groups, namely pregnant women who regularly did pregnancy exercise and a control group, namely pregnant women who did not take part in pregnancy exercise. The research population was all TM III pregnant women, totaling 40 people. The sample technique used was total sempling with a 1:1 ratio of 20 respondents per group. Test analysis resultsT Test p-Value <? (0.000 <0.05) was obtained. Based on this test, it can be concluded that there is an effect of participating in pregnancy exercise on the anxiety level of Tm III mothers to deal with childbirth at the Serpong Healthy Pregnancy Clinic in the intervention and control group, after participating in routine pregnancy exercise ± 4 times